2015
DOI: 10.1016/j.cell.2015.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Feedback from Network States Generates Variability in a Probabilistic Olfactory Circuit

Abstract: Variability is a prominent feature of behavior and is an active element of certain behavioral strategies. To understand how neuronal circuits control variability, we examined the propagation of sensory information in a chemotaxis circuit of C. elegans where discrete sensory inputs can drive a probabilistic behavioral response. Olfactory neurons respond to odor stimuli with rapid and reliable changes in activity, but downstream AIB interneurons respond with a probabilistic delay. The interneuron response to odo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
293
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(327 citation statements)
references
References 60 publications
34
293
0
Order By: Relevance
“…It remains to be seen whether independent calcium dynamics in the processes are unique to these few specific neurons or are a more general phenomenon. For example, a recent investigation of three C. elegans interneurons found that calcium activity peaked more quickly in the process than the cell body but was otherwise similar (29). Although it is tempting to try to explore neural dynamics in the processes by expressing a calcium indicator in the cytoplasm of all neurons, pan-neuronal cytoplasmic expression of a fluorophore is impractical for segmenting individual processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be seen whether independent calcium dynamics in the processes are unique to these few specific neurons or are a more general phenomenon. For example, a recent investigation of three C. elegans interneurons found that calcium activity peaked more quickly in the process than the cell body but was otherwise similar (29). Although it is tempting to try to explore neural dynamics in the processes by expressing a calcium indicator in the cytoplasm of all neurons, pan-neuronal cytoplasmic expression of a fluorophore is impractical for segmenting individual processes.…”
Section: Discussionmentioning
confidence: 99%
“…24 and and then developing rapidly (17,18,(25)(26)(27)(28)(29). One limitation of these freely moving calcium imaging systems is that they are limited to imaging only a very small subset of neurons and lack the ability to distinguish neurons that lie atop one another in the axial direction of the microscope.…”
mentioning
confidence: 99%
“…Action selection in nematodes is driven by shifts in global brain dynamics (119), and there is sufficient plasticity in the nematode nervous system for their responses to vary with system state (120). However, there is no evidence that nematodes can actively hunt for things beyond their immediate sensory environment.…”
Section: Beyond Insectsmentioning
confidence: 99%
“…Thus, one interesting possibility is that olfactory and mechanosensory information about food availability converge at the level of premotor and motor neurons. Notably, recent work demonstrates the activity state of some premotor interneurons downstream of chemosensory neurons can have profound effects on neural responses to odors, 21 providing an additional avenue by which peptide modulation of premotor and motor activity may shape local search responses.…”
Section: The Interneuron Dva and Local Search Behaviormentioning
confidence: 99%